Polish version of the Aesthetic Experience Questionnaire: validation and psychometric characteristics - Świątek, Agata Hiacynta; Szcześniak, Małgorzata; Wojtkowiak, Karolina; Stempień, Michał; Chmiel, Marianna (Frontiers in Psychology, 2023)
The purpose of the article is to present the results of works on the Polish version of the Aesthetic Experience Questionnaire (AEQ). The AEQ is a 22-item tool for assessing aesthetic experience in the following dimensions: emotional, cultural, perceptual, understanding, and two dimensions about flow (proximal conditions and flow experience). In the course of works on the Polish version of the AEQ, 3 independent studies with the participation of more than 800 people were carried out. In addition to the AEQ measurement, the tools included: the Emotion